Meningkatkan Hasil Belajar Peserta Didik dengan Penerapan Model Problem Based Learning Melalui Pembelajaran Daring Terhadap Peserta Didik Kelas III SD Negeri Tlogomulyo - Uswatun Khasanah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The purpose of this research is to find out the level of achievement og learner’s learningoutcomes in learning, as well as the ability of learner’s in applying learning materials ineveryday life through online learning. The model used in this learning is the ProblemBased Learning (PBL) model with the research subject of class III learner’s at TlogomulyoTemanggung State Elementary School which numbered 17 learners. The result of thestudy obtained the percentage of learning outcomes of learner knowledge from cycle I tocycle II increased, reaching 17,65%, then the percentage of learning outcomes of learner’sattitude increased by 11,77%, then the percentage of learning outcomes of learner’s skillsincreased by 23,53%. The method in this research is a class action research method. Thedata collection in this study was using tests. The result showed that with the applicationof the Problem Based Learning (PBL) model can increase the learning outcomes oflearners, it can be seen from many learners who become more active in asking questionsduring learning and begin to dare to express opinion.